Cirrhotic Cardiomyopathy Predicts Posttransplant Cardiovascular Disease: Revelations of the New Diagnostic Criteria. Issue 6 (8th June 2021) - Izzy, Manhal; Soldatova, Anna; Sun, Xin; Angirekula, Mounika; Mara, Kristin; Lin, Grace; Watt, Kymberly D.
Abstract : The diagnostic criteria for cirrhotic cardiomyopathy (CCM) were recently revised to reflect the contemporary advancements in echocardiographic technology. This study evaluates the prevalence of CCM, according to the new criteria, and its impact on posttransplant cardiovascular disease (CVD). This is a single‐center retrospective matched cohort study of liver transplantation (LT) recipients who underwent LT between January 1, 2008 and November 30, 2017. A total of 3 cohorts with decompensated cirrhosis (nonalcoholic steatohepatitis, alcohol‐related liver disease, or other etiologies) were matched based on age, sex, and year of transplant after excluding patients listed without evidence of hepatic decompensation. CCM was defined, according to 2020 criteria, as having diastolic dysfunction, left ventricular ejection fraction ≤50%, and/or a global longitudinal strain (GLS) absolute value <18%. The study echocardiographers were blinded to the clinical data. Posttransplant CVD included new coronary artery disease, congestive heart failure, atrial and ventricular arrhythmia, and stroke. The study included 141 patients of whom 59 were women. The mean age at LT was 57.8 (±7.6) years. A total of 49 patients (34.8%) had CCM. Patients with CCM were at an increased risk for post‐LT CVD (hazard ratio, 2.57; 95% confidence interval, 1.2‐5.5; P = 0.016). Changes in CCM individual parameters pretransplant, such as GLS, early diastolic transmitral flow to early diastolic mitral annular velocity, and left atrial volume index were associated with an increased risk for posttransplant CVD. CCM, defined by the new diagnostic criteria, affects approximately one‐third of decompensated LT candidates. CCM predicts an increased risk for new CVD following LT. Studies into addressing and follow‐up to mitigate these risks are needed. Abstract : https://www.wileyhealthlearning.com/Activity2/7356951/Activity.aspx